LA COMPRENSIÓN HERMENÉUTICA: UN ACERCAMIENTO PSICOANALÍTICO Y SOCIO-HISTÓRICO A LA INTERPRETACIÓN DE TEXTOS MÍTICOS Y LITERARIOS - Hidalgo Xirinachs, Roxana (2023)
In this work the methodological foundations of mythical and the hermeneutics literary text understanding are explored as much in the psychoanalytic level as in the socialhistorical one. By means of a social-psychoanalytic understanding of the artistic creation, the literary form like intermediate space between the symbolization and the non-symbolization of unconscious conflicts in the text interpretation is analyzed. The counter-transference function analysis plays an essential role in the text interpretation. In this sense, not only the analysis of the relation between the interpreter and the text as counter-transferencial space is important, but also the contrast of the own interpretation with other interpretations of the text reception history. Besides, it has to be taking into account the social and cultural contexts in which the text was written and the theoretical-conceptual fundamentals where the investigation is constructed on.